Strategi Dinas Sosial Dalam Penanganan Anak Jalanan Di Kota Tanjungpinang - Thariq Riawan; Jamhur Poti; Ramadhani Setiawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Street children are not a pleasant choice because they are in a state of uncertainty about their future, and their existence is not a